Grinding against HIV discourse: a critical exploration of social sexual practices in gay cruising apps. (2nd September 2019) - Numer, Matthew; Holmes, Dave; Joy, Phillip; Thompson, Ryan; Doria, Nicole
Abstract: Social networking applications (SNAs), such as Grindr, are shaping the identities and sexual practices of gay, bisexual and other men who have sex with men (GBM). This qualitative study aimed to gain a deeper understanding of the role of such technologies in social sexual practices, particularly in relation to risk management and prevention of HIV and other sexually transmitted blood-borne infections (STBBIs). Poststructuralism and queer theory were used to critically examine the relationship between GBM and SNAs in a sample of people who use Grindr . Sixteen people, identifying as men who used Grindr, were interviewed. Discourse analysis was employed to critically examine the relationship between GBM and SNAs, and three threads of discourse emerged: Language and images, Filtering, and Trust . These threads of discourse provide insight into how the sexual beliefs, values, and practices of GBM are shaped on SNAs.